Religious Moderation: Interfaith Harmony in Bandar Village - Muhammad Bahrul Ulum; Marsaa Baihaqi; Diniyatul Munawaroh (Jurnal Indonesia Studi Moderasi Beragama, 2024)
Background: Indonesia’s multicultural society presents both opportunities and challenges for maintaining inter-religious harmony. In local communities with religious diversity, the practice of tolerance is essential to support peaceful coexistence and national unity. Objective: The purpose of this study is to determine how inter-religious harmony is implemented in Bandar Village, which is known for its religious diversity. Method: This research employs a field research method conducted in 2023 in Bandar Village, Bandar District, Batang Regency. Data were collected through in-depth interviews and direct observation, and analyzed using content analysis. Result: The findings reveal that Bandar Village residents, despite their religious differences, exhibit strong tolerance and mutual respect. Their religious beliefs are deeply rooted from birth and are not influenced or disrupted by external religious pressures. Conclusion: Bandar Village demonstrates a successful model of inter-religious harmony, where strong internal beliefs and mutual acceptance foster a peaceful and respectful community life. Contribution: This study provides a valuable reference for understanding the practical application of religious moderation in a multicultural society and offers insights for replicating similar approaches in other diverse communities to sustain harmony and unity.